(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses the main environmental factors affecting the development of small businesses. Each organization, regardless of its organizational and legal form and the scale of the organization, interacts with the external environment. Due to the external environment, the organization is provided with the necessary resources necessary to maintain its activities. Today, a difficult economic situation has formed in many countries, including Azerbaijan. In this regard, the external environment has become unstable, which in turn affects small businesses.